Total Synthesis of Skipped Diene Natural Products. Issue 10 (31st August 2021) - Sato, Takaaki; Suto, Takahiro; Nagashima, Yoshiyuki; Mukai, Shori; Chida, Noritaka
Abstract: Skipped dienes (1, 4‐dienes) are widely distributed in a variety of biologically active natural products. The synthesis of these skipped dienes is a relatively undeveloped area compared with that of conjugated dienes (1, 3‐dienes) due to the sp 3 ‐hybridized carbon between two olefins. Especially, development of methods to meet both high stereoselectivity and convergency is highly challenging. This review focuses on recent advances in the synthesis of skipped dienes in the total synthesis of complex natural products, which are classified into three classes; a) skipped dienes comprised of two disubstituted olefins, b) skipped dienes including trisubstituted olefin(s), and c) 3‐methyl skipped dienes. Abstract : The synthesis of skipped dienes (1, 4‐dienes) is a relatively undeveloped area compared with that of conjugated dienes (1, 3‐dienes) due to the sp 3 ‐hybridized carbon between two olefins. Especially, development of methods to meet both high stereoselectivity and convergency is challenging. This review focuses on the recent progress of synthesis of the skipped dienes in total synthesis of complex natural products.